A CONTRASTIVE ANALYSIS OF USING NOUN PHRASE IN ENGLISH AND INDONESIAN LANGUAGE BY USING YOUTUBE VIDEO - Anita Sitanggang; Artha Yuni Trimedia Situngkir; Dwira May Situmorang (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
The goal of this study is to explain the distinctions between the types of noun phrases and how they are used in English and Indonesian. This study was based on the observation that university-level students frequently make errors while adapting the grammar of their home language (L1) to that of the target language (L2), particularly when translating noun phrases (NP) from English to Indonesian. In the research process, content analysis is used. The scientific text "The Legend of Batu Gantung" and its translated version served as the research data source. A person is hanged from a tree in the Batu Hanging tradition, which originates in the Lake Toba region of North Sumatra. There was a legend about a stunning young woman named Seruni. He killed himself because his father would wed him to either his pariban or his namboru child. Nouns are the words used to refer to individuals, places, or objects in the English language. A noun phrase (NP) is a collection of words that operates like a noun, typically including a noun and a modifier (such as an adjective, adverb, or article). In Indonesia, there are several different kinds of noun phrases, including Modificative, Coordinative, and Appositive NPs. While Head, Determiners, Premodifiers, and Postmodifiers are used in English. The study's findings demonstrate that there are differences in NP usage in English and Indonesian in addition to NP type.